Faktor-Faktor yang Berhubungan dengan Tindakan Petugas Kesehatan di Puskesmas Pasar Rebo Jakarta Timur dalam Upaya Pencegahan HIV AIDS - Eliya Eliya; Diana Barsasella (Jurnal Persada Husada Indonesia, 2015)
This research addresses the issue of AIDS disease which is a collection of symptoms caused bydecreased immune system from HIV virus. This disease cause the world unrest, due to the rapid spread likegeometrical progression, undetected patients as an iceberg phenomenon and means of prevention and effective treatment has not been found. DKI Jakarta has a large number of HIV AIDS patients in Indonesia, and East Jakarta District has the highest number compared with other district in Jakarta. The objective of this study is to determine the factors associated with health workers in the prevention of HIV/AIDS at Puskesmas Pasar Rebo, East Jakarta. The purpose of this research is to analyze the relationship between predisposing, enabling, and reinforcing factors of health workers activity in the prevention of HIV-AIDS. The research method is a nonexperimental study of quantitative research and the data collected by cross sectional method. The research location, Puskesmas Pasar Rebo, East Jakarta. The research sample is taken from the health workers (doctors, nurses, midwives, SKM) who work for Puskesmas Pasar Rebo. The data collected by interview using a structured questionnaire. The data were analyzed using univariate and bivariate.